Decompressive craniectomy in a rat model of "malignant" cerebral hemispheric stroke: experimental support for an aggressive therapeutic approach - Dörfler, Arnd; Forsting, Michael; Reith, Wolfgang; Staff, Christian; Heiland, Sabine; Schäbitz, Wolf-Rüdiger; Kummer, Rüdiger von; Hacke, Werner; Sartor, Klaus (Journal of neurosurgery, 1996)
✓ Acute ischemia in the complete territory of the carotid artery may lead to massive cerebral edema with raised intracranial pressure and progression to coma and death due to uncal, cingulate, or tonsillar herniation. Although clinical data suggest that patients benefit from undergoing decompressive surgery for acute ischemia, little data about the effect of this procedure on experimental ischemia are available. In this article the authors present results of an experimental study on the effects of decompressive craniectomy performed at various time points after endovascular middle cerebral artery (MCA) occlusion in rats. Focal cerebral ischemia was induced in 68 rats using an endovascular occlusion technique focused on the MCA. Decompressive cranioectomy was performed in 48 animals (in groups of 12 rats each) 4, 12, 24, or 36 hours after vessel occlusion. Twenty animals (control group) were not treated by decompressive craniectomy. The authors used the infarct volume and neurological performance at Day 7 as study endpoints. Although the mortality rate in the untreated group was 35%, none of the animals treated by decompressive craniectomy died (mortality 0%). Neurological behavior was significantly better in all animals treated by decompressive craniectomy, regardless of whether they were treated early or late. Neurological behavior and infarction size were significantly better in animals treated very early by decompressive craniectomy (4 hours) after endovascular MCA occlusion (p < 0.01); surgery performed at later time points did not significantly reduce infarction size. The results suggest that use of decompressive craniectomy in treating cerebral ischemia reduces mortality and significantly improves outcome. If performed early after vessel occlusion, it also significantly reduces infarction size. By performing decompressive craniectomy neurosurgeons will play a major role in the management of stroke patients.